Que ciência da informação precisamos para enfrentar a complexidade? - Silva, Armando Malheiro da (2017)
A scientific meeting with tradition and consistency like this that brings us together has supportedespecially by those who have dedicated work and enthusiasm for teaching and research in InformationScience, it is imperative to reflect on the challenges facing this course in itself complex, in front of anoverall framework of maximum complexity. A discipline that lack consensus among its practitioners andlearners about the natural matrix - interdisciplinary or trans and interdisciplinary? - and the more generalfield of integration - Social Sciences or Information and Communication Technologies? Giventhatthereis aseriousepistemological debate deficitthat ENANCIB haveservedtofill, althoughthereis a needandroom formore. It is intended here to discuss the internal, external and training plan of the CI the ways that it is urgentto draw and make a was challenging as the one we are experiencing, starting from recent milestonespublished to signal the state of discipline in certain socio-cultural landscapes, particularly the Anglo-American and Nordic-Germanic. The call to reflection and constructive debate, if heeded is a precious andworth gain, so that we contribute to it